Development of Multifunctional Futsal Goal posts for Physical Education Learning in Elementary Schools, Selosari Village, Kediri Regency - Alam, Bima Tangguh; Pramono, Harry; Rumini, Rumini (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The purpose of this study are: (1) developing multifunctional futsal goalposts for sports and health physical education learning materials, (2) providing learning tools to be more effective and efficient for physical education. The procedure of development research carried out includes several activities including: (1) initial analysis; (2) analysis of needs during sports and health physical education learning (3) analysis of manufacture counts; (4) planning the initial product; (5) expert validation; (6) revisions; (7) small scale trials; (8) revisions; (9) product testing; (10) revisions. The instruments used in this study include (1) assessment sheet/questionnaire; (2) interviews. The results of the validation of material experts I and II which covered all aspects obtained an average value of 88% and 83% with very good categories, while the validation of technical experts I and II obtained an average percentage value that included all aspects of 82% and 85% with very good categories. In small-scale trials, the percentage value obtained by respondents of students and sports and health physical education teachers was 92% and 90% with very good categories. The results of large-scale product testing obtained an average value of percentages with respondent respondents by 95% with a very good category and the respondents are physical education teachers obtained an average value of 94% with the category obtained very well. The conclusions and suggestions in this study resulted in a multifunctional futsal goalpost product for physical education for elementary school students. Suggestions for multifunctional goalpost products can be applied in elementary schools especially in physical education subjects.